The Metabolite Transporters of the Plastid Envelope: An Update - Facchinelli, Fabio; Weber, Andreas P. (Frontiers in Plant Science, 2011)
The engulfment of a photoautotrophic cyanobacterium by a primitive mitochondria-bearing eukaryote traces back to more than 1.2 billion years ago. This single endosymbiotic event not only provided the early protoalga with the metabolic capacity to perform oxygenic photosynthesis, but also introduced a plethora of other metabolic routes ranging from fatty acids and amino acids biosynthesis, nitrogen and sulfur assimilation to secondary compounds synthesis. This implicated the integration and coordination of the newly acquired metabolic entity with the host metabolism. The interface between the host cytosol and the plastidic stroma became of crucial importance in sorting precursors and products between the plastid and other cellular compartments. The plastid envelope membranes fulfill different tasks: they perform important metabolic functions, as they are involved in the synthesis of carotenoids, chlorophylls and galactolipids. In addition, since most genes of cyanobacterial origin have been transferred to the nucleus, plastidial proteins encoded by nuclear genes are post-translationally transported across the envelopes through the TIC-TOC import machinery. Most importantly, chloroplasts supply the photoautotrophic cell with photosynthates in form of reduced carbon. The innermost bilayer of the plastidic envelope represents the permeability barrier for the metabolites involved in the carbon cycle and is literally stuffed with transporter proteins facilitating their transfer. The intracellular metabolite transporters consist of polytopic proteins containing membrane spans usually in the number of four or more α-helices. Phylogenetic analyses revealed that connecting the plastid with the host metabolism was mainly a process driven by the host cell. In Arabidopsis, 58% of the metabolite transporters are of host origin, whereas only 12% are attributable to the cyanobacterial endosymbiont. This review focuses on the metabolite transporters of the inner envelope membrane o